Risk shifting versus risk management investment policy in corporate pension plans - Rauh, Joshua (Working paper series / National Bureau of Economic Research, 2007)
The asset allocation of defined benefit pension plans is a setting where both risk shifting and risk management incentives are likely be present. Empirically, firms with poorly funded pension plans and weak credit ratings allocate a greater share of pension fund assets to safer securities such as government debt and cash, whereas firms with well-funded pension plans and strong credit ratings invest more heavily in equity. These relations hold both in the cross-section and within firms and plans over time. The incentive to limit costly financial distress plays a considerably larger role than risk shifting in explaining variation in pension fund investment policy among U.S. firms.